Short- and Long-Term Functional Consequences of Fluoxetine Exposure During Adolescence in Male Rats - Iñiguez, Sergio D. (2010)
BACKGROUND: Fluoxetine (FLX), a selective serotonin reuptake inhibitor, is prescribed for the treatment of major depressive disorder in young populations. Here, we explore the short- and long-term consequences of adolescent exposure to FLX on behavioral reactivity to emotion-eliciting stimuli. METHODS: Adolescent male rats received FLX (10 mg/kg) twice daily for 15 consecutive days (postnatal days 35–49). The influence of FLX on behavioral reactivity to rewarding and aversive stimuli was assessed 24 hours (short-term) or 3 weeks after FLX treatment (long-term). A separate group of adult rats was also treated with FLX (postnatal days 65–79) and responsiveness to forced swimming was assessed at identical time intervals as with the adolescents. RESULTS: Fluoxetine exposure during adolescence resulted in long-lasting decreases in behavioral reactivity to forced swimming stress and enhanced sensitivity to sucrose and to anxiety-eliciting situations in adulthood. The FLX-induced anxiety-like behavior was alleviated by re-exposure to FLX in adulthood. Fluoxetine treatment during adolescence also impaired sexual copulatory behaviors in adulthood. Fluoxetine-treated adult rats did not show changes in behavioral reactivity to forced swim stress as observed in those treated during adolescence and tested in adulthood. CONCLUSIONS: Treating adolescent rats with FLX results in long-lived complex outputs regulated by the emotional valence of the stimulus, the environment in which it is experienced, and the brain circuitry likely being engaged by it. Our findings highlight the need for further research to improve our understanding of the alterations that psychotropic exposure may induce on the developing nervous system and the potential enduring effects resulting from such treatments.